2020
DOI: 10.1039/d0an01148g
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics for label-free sorting of rare circulating tumor cells

Abstract: Circulating tumor cells (CTCs) have been widely considered as promising novel biomarkers for molecular research and clinical diagnosis of cancer. However, the sorting of CTCs is very challenging due to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 177 publications
0
46
0
Order By: Relevance
“…Most of the available immune-based microfluidic systems utilize positive selection of CTCs, and rely on epithelial cell adhesion molecule, EpCAM, a transmembrane glycoprotein, expression. EpCAM is a surface marker commonly used to detect CTCs, since it is present in tumor cells derived from human epithelial tumors, but absent in blood cells [ 70 , 73 ]. CTC-chip, a microfluidic device for CTCs detection containing microposts coated with antibodies against EpCAM molecule was first introduced by Nagrath et al The chip detected CTCs in 115 of 116 (99%) samples from patients with metastatic breast, colon, lung, prostate, and pancreatic cancer with 50% purity and a range of 5–1281 CTCs per sample ml of blood [ 74 ].…”
Section: Lab-on-a-chip Approaches For Liquid Biopsiesmentioning
confidence: 99%
“…Most of the available immune-based microfluidic systems utilize positive selection of CTCs, and rely on epithelial cell adhesion molecule, EpCAM, a transmembrane glycoprotein, expression. EpCAM is a surface marker commonly used to detect CTCs, since it is present in tumor cells derived from human epithelial tumors, but absent in blood cells [ 70 , 73 ]. CTC-chip, a microfluidic device for CTCs detection containing microposts coated with antibodies against EpCAM molecule was first introduced by Nagrath et al The chip detected CTCs in 115 of 116 (99%) samples from patients with metastatic breast, colon, lung, prostate, and pancreatic cancer with 50% purity and a range of 5–1281 CTCs per sample ml of blood [ 74 ].…”
Section: Lab-on-a-chip Approaches For Liquid Biopsiesmentioning
confidence: 99%
“…To this end, inertial microfluidics is attractive since the active and passive, sizebased, technology exploits inherent surface property and hydrodynamic forces that scale with increased flow rate and among them spiral channel designs have been shown to operate at extremely high volumetric flow rates (∼mL/min) [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. However, microfluidic technology has been utilized extensively to precisely focus and separate mammalian cells, including circulating tumor cells [34][35][36][37][38][39][40][41][42][43][44][45][46], but the separation of small-sized bacteria from blood has been challenging. The main challenge in inertial microfluidics-based bacteria separation is due to the narrow size difference between bacteria (∼1-2 μm) and blood cells (∼3-15 μm).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that there are differences in the biological and physical characteristics between CTCs and blood cells (e.g., biomarkers, size, density, and deformability) ( Ferreira et al, 2016 ). Based on these properties, immunomagnetic bead capture ( Markou et al, 2011 ; Chang et al, 2020 ; Wu et al, 2020 ), filtering systems ( Chang et al, 2015 ; Yoshino et al, 2016 ; Xia et al, 2018 ), and microfluidics ( Patil et al, 2015 ; Abdulla et al, 2020 ; Zhu et al, 2020 ) have been developed to isolate CTCs. The CellSearch system, which utilizes immunomagnetic beads coupled with antibodies to identify and isolate CTCs under the effect of external magnetic fields ( Riethdorf et al, 2007 ), has good specificity, and the principle is simple.…”
Section: Introductionmentioning
confidence: 99%